Pembelajaran Kolaboratif untuk Pengajaran Keterampilan Membaca Bahasa Arab di Madrasah Aliyah - Husein, Sudi Yahya; Munawaroh, Roudhotul Jannah; Firmansyah, Firmansyah (Department of Arabic Education - Faculty of Educational Sciences, 2022)
Arabic learners often face various difficulties in reading activities. The research used the quantitative approach of the experimental method by non-equivalent control group design. The study population for this research is 60 students. The 30 students are decided to represent the experimental group and 30 students to represent the control group. The researcher used the t-test rule in analyzing the data to reveal the effectiveness of using cooperative learning strategy. As for the methods that the researcher used in all of them, they are: direct observation, personal interview, pre and post written test. The researcher concluded that the use of the cooperative learning strategy in the reading skill of pupils in this school is effective.